Composition manipulation of heat-resistant iron-based cores@graphitic carbon@amorphous carbon derived from urea-modulated MOFs for high-efficient microwave absorption. Issue 16 (15th August 2022) - Liu, Jue; Cao, Qian; Meng, Can; Li, Shiwen; Pang, Jianming; Dong, Xiaoping; Li, Chunhua
Abstract: Designing multifunctional microwave absorption materials is crucial in practical application. Herein, the iron-based cores@graphitic carbon@amorphous carbon composites with diverse phase compositions were annealed from urea-modulated metal organic frameworks (MOFs), MIL-88A, as precursors. By simply varying the mass ratio of urea and MIL-88A, the chemical compositions of as-prepared samples were well adjusted, which brought the variation of interfacial polarization, dipole polarization, and magnetic response. Meanwhile, the structure with outer-layered amorphous carbon and inner-layered graphitic carbon enhanced impedance matching. Therefore, with stronger microwave attenuation brought by polarization loss and better impedance matching, the high-efficient microwave absorption performance with a minimum reflection loss ( R L ) of −67.81 dB at 12.5 GHz and an effective absorption bandwidth of 5.76 GHz was obtained with S-05 (Fe/Fe3 C/Fe15.1 C@graphitic carbon@amorphous carbon), which was prepared with the weight ratio of MIL-88A and urea at 2:1. Meanwhile, the iron-based cores@graphitic carbon@amorphous carbon composites possess good heat-resistant properties due to the existence of protecting carbon layers. Thus, urea-assisted treatment paves a way for acquiring multifunctional absorbers derived from MOFs with enhanced microwave absorption performance.